2022
DOI: 10.3389/fnut.2022.925642
|View full text |Cite
|
Sign up to set email alerts
|

The Pulsed Electric Field Assisted-Extraction Enhanced the Yield and the Physicochemical Properties of Soluble Dietary Fiber From Orange Peel

Abstract: The study aimed to investigate the effects of pulsed electric field (PEF)-assisted extraction on the yield, physicochemical properties, and structure of soluble dietary fiber (SDF) from orange peel. The results showed that the optinal parameters of PEF assisted extraction SDF was temperature of 45oC with the electric field intensity of 6.0 kV/cm, pulses number of 30, and time of 20min and SDF treated with PEF showed the higher water solubility, water-holding and oil-holding capacity, swelling capacity, emulsif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 71 publications
(94 reference statements)
0
11
0
Order By: Relevance
“…In contrast, a decreasing trend in LGC can be observed from 11.26 ± 0.71% (E-SDF) to 8.18 ± 0.28% (PEF-SDF; p < 0.05). The results showed that PEF-SDF has better gelation properties ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a decreasing trend in LGC can be observed from 11.26 ± 0.71% (E-SDF) to 8.18 ± 0.28% (PEF-SDF; p < 0.05). The results showed that PEF-SDF has better gelation properties ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Water-related properties, including WHC and SC, have been reported to be associated with DF individual components, including molecular size and structure (network density and porosity) ( 46 ). It was speculated that the larger the WHC and SC values of PEF-SDF and M-SDF, the greater the proportion of short-chain dietary fiber ( 32 , 49 ). Similarly, the higher OHC values of PEF-SDF and M-SDF might be associated with more complex porous structures and surface areas, which is consistent with a previous report ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEF-assisted by the phenomenon of electropermeabilization reduces extraction time, diminishes the necessity for intense heating processes, and minimizes the reliance on solvents. 16,19,105 PEF-assisted extraction processes support the conceptions of green chemistry and sustainability. PEF technology by increasing the mass transfer of intracellular components allow the use of eco-friendly solvents for extracting natural colorants and bioactive compounds, preventing the contamination of food and beverages with harmful chemicals.…”
Section: Benets and Main Limitationsmentioning
confidence: 99%
“…PEF-assisted by the phenomenon of electropermeabilization reduces extraction time, diminishes the necessity for intense heating processes, and minimizes the reliance on solvents. 16,19,105…”
Section: Pef Technology For Valorization Of Agro-industrial Wastementioning
confidence: 99%